Effect of solvent polarity on secondary metabolite content and α-glucosidase enzyme IC50 of Dendrophthoe pentandra (L). Miq leaves extract - Subandrate, Subandrate; Sinulingga, Sadakata; Adma, Annes Claudia; Monanda, M. Dias Athallah; Fatmawati, Fatmawati; Safyudin, Safyudin; Oswari, Liniyanti D (Faculty of Pharmacy, Universitas Pancasila, 2024)
Cherry mistletoe (Dendrophthoe pentandra (L). Miq) have an inhibitory effect on the α-glucosidase enzyme, but research related to solvent optimization to find active compound is unclear. Secondary metabolites that can be identified depend on the level of solvent polarity. This study aims to determine the effect of solvent polarity on the secondary metabolite content and the α-glucosidase enzyme by using the polar and nonpolar fractions of the ethyl acetate extract of cherry mistletoe leaves. Cherry mistletoe leaves were extracted using ethyl acetate and were followed by a liquid-liquid fractionation. The polar fraction used ethanol and ethyl acetate as solvents, whereas the nonpolar fraction used n-hexane and ethyl acetate as solvents. Secondary metabolites present in polar fractions were alkaloids, flavonoids, steroids, tannins, and terpenoids, whereas those present in nonpolar fractions were flavonoids and steroids. The IC50 value of the polar fraction (54.8 ppm) was lower than that of the nonpolar fraction (192.0 ppm). The polar fraction of the ethyl acetate extract of cherry mistletoe leaves could inhibit the α-glucosidase enzyme and, therefore, is classified as active. On the other hand, the nonpolar fraction of the ethyl acetate extract of cherry mistletoe leaves could not inhibit the α-glucosidase enzyme and, therefore, is classified as inactive in general.